Beyond technological explanations of employment polarisation in Spain - Raquel Sebastian; Scott Harrison (Global Labor Organization (GLO), 2017)
This paper presents new evidence on the evolution of job polarisation over time and across skill groups in Spain between 1994 and 2008. Spain has experienced job polarisation over the whole period, with growth at the upper part of the wage distribution always exceeding that in the lower part. Results show that the decline in the middle-occupations is accounted by non-graduates and pushing their reallocation at the bottom part of the occupational skill distribution. The growth at the top occupations is explained by compositional changes, as a result of the increase in the number of graduates. Therefore, this study has demonstrated that education plays an important factor. Researchers need to go beyond technological explanations for job polarisation, not just in Spain, but possibly globally.
Keywords: J21; J23; J24; O33; 330; Job Polarisation; Spain; occupational mobility; Technological Change